UK levelling up R&D mission effects: A multi-region input-output approach - Huanjia Ma; Raquel Ortega-Argiles; Matthew Lyons (The University of Manchester, The Manchester Institute of Innovation Research (MIoIR), 2024)
This paper examines the UK implications for regional and national growth associated with different geographical investment patterns of publicly-funded R&D, in the light of the recommendations of the 2022 Levelling Up White Paper, aimed at balancing the national economy. The White Paper outlines twelve main "missions" focused on science, technology, and education to achieve this goal. One of these missions aims to increase domestic public Research and Development (R&D) by at least 40% outside the Greater South East (GSE) by 2030. We develop three scenarios based on different assumptions about extra R&D allocation. We use data from UKRI and ONS to determine the current distribution of R&D investment in the UK, and then using the multi-regional Socio-Economic Impact Model for the UK we evaluate our three proposed R&D spending scenarios. Our findings suggest that the regional impact varies significantly across the different proposed scenarios. The scenario that allocates more GERD to areas with previously low funding levels yields the largest effect. On average, output, employment and GVA in regions outside GSE increase by 0.33%, 0.37% and 0.34%, respectively, showing a potentially positive effect on the levelling up of R&D in the country. Our analysis of both internal and external multipliers highlights the importance of investing in regional redistribution. We demonstrate that the GSE is more self-sufficient as it has much higher internal multipliers than the rest of the UK. However, we identified a potential obstacle: the capacity to absorb human capital, which could reduce the expected positive results of a more spatially balanced R&D expenditure across the UK.
Keywords: 330; Multi-region input-output; R&D; Levelling-up; UK